China's emerging global middle class - Björn Gustafsson; Terry Sicular; Xiuna Yang (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
This chapter seeks to throw new light on the emergence of the Chinese economic middle class using data from the China Household Income Project from 2002, 2007, and 2013. We find that between 2002 and 2013 China's income distribution was transformed from a pyramid shape, with a majority having rather low income, to a more olive shape, as the middle class emerged. Defining "middle class" as having an income high enough not to be regarded as poor but also low enough not to be regarded as rich if living in a high-income country, we find that the share of China's population that was middle class was extremely small in 2002, larger but still less than 10 percent in 2007, but it expanded rapidly from 2007 to 2013 to become one-fifth of China's population, equivalent to roughly 250 million people. China's middle class remains largely urban and is concentrated in the East; only a small minority of rural households and of rural migrants living in urban areas is middle class. We use simulations to investigate whether the growth of China's middle class reflects across-the-board income growth versus a redistribution of income to the middle, and to project growth in the size of the middle class to 2020. If all household incomes grow uniformly by 6.5 percent per annum to 2020, then China's middle class will almost double in size and in 2020 a majority of urban residents, but only 13 percent of rural residents, will be classified as middle class. We examine the characteristics of China's middle class and find it to be distinctive in terms of its sources of income, location of residence, savings and consumption patterns, education, and Communist Party membership.
Keywords: D31; O15; O53; P36; 330; China; middle class; income distribution